Identificação molecular de herpesvírus bovino tipos 1 e 5 - Silva, Mariana Sá e (2009)
Bovine herpesvirus types 1 and 5 (BoHV-1, BoHV-5) are genetically and antigenic related viruses and have been associated with important economic losses to the cattle industry. The aim of this Thesis was to perform the molecular identification of BoHV-1 and BoHV-5 isolates. The first part describes the identification of 40 herpesviruses isolated from different clinical specimens and syndromes in central-southern Brazil, Argentina and Uruguay (1987 2006). The differentiation between BoHV-1 and BoHV-5 was performed by examining the size of the amplification product of a glycoprotein C gene-based PCR, designed for a low homology region of the gene. BoHV-1 isolates (n=16) were identified in cases of respiratory disease (n=3), vulvovaginitis and/or balanoposthitis (n=3), in semen of healthy bulls (n=5) and in cases of neurological disease (n=5). Samples identified as BoHV-5 (n=24) were isolated predominantly from cases of neurological disease (n=21), but also from semen of healthy bulls (n=2) and from a spleen of a calf with systemic disease (n=1). These results show that both BoHV-1 and BoHV-5 are not strictly associated with their respective diseases; yet are frequently involved in clinical conditions otherwise attributed to the other virus type. These findings also reinforce the need of correctly identifying the herpesvirus isolates as to better understand their pathogenesis and epidemiology. In the second part, it is reported the characterization of five Brazilian BoHV-1 isolates associated with neurological disease, an unusual finding. All five samples were isolated from the brain of cattle presenting neurological disease, yet histological evidences of meningoencephalitis were not observed in three cases. The isolated viruses were identified as BoHV-1 by a glycoprotein C gene-based PCR able to differentiate BoHV-1 from BoHV-5. The identity of the isolates was confirmed by nucleotide sequencing of the amplicons and by restriction analysis of PCR products from another gC region. Monoclonal antibody binding and cross-neutralization assays with BoHV-1 and BoHV-5 antisera showed a typical BoHV-1 antigenic profile. Inoculation of rabbits with these five BoHV-1 isolates did not result in neurological disease, contrasting with fatal meningoencephalitis produced by BoHV-5. Thus, the involvement of BoHV-1 in neurological disease of cattle is more frequent than previously reported, indicating the need for fast and precise means of differentiating it from BoHV-5. Likewise, the potential role of BoHV-1 in neurological disease in cattle should be further investigated.